(untitled) (Al-NASR, 2024)
This study offers a critical and analytical examination of the scholarly contributions of J. M. S. Baljon to the study of Qur’anic interpretation, with particular emphasis on the emergence and development of rationalist trends in modern Muslim thought. Through an in-depth analysis of Baljon’s major works—especially Religion and Thought of Shah Wali Allah Dihlawi and Modern Muslim Koran Interpretation (1880–1960)—the paper explores how Qur’anic exegesis evolved in response to intellectual, scientific, and socio-political challenges of the modern era. The study highlights Baljon’s methodological approach, including his extensive use of primary sources, historical contextualization, and comparative engagement with both classical Islamic scholarship and modern Western academic frameworks. Special attention is given to his analysis of influential Muslim thinkers such as Shah Wali Allah Dihlawi and Sir Sayyid Ahmad Khan, whose efforts to harmonize reason and revelation played a pivotal role in shaping modern Qur’anic hermeneutics. While acknowledging the strengths of Baljon’s research—its academic rigor, breadth, and critical insight—the study also identifies certain limitations, particularly his limited engagement with the political and economic dimensions of Islamic thought. The paper concludes that Baljon’s work remains a foundational reference for understanding the intellectual transition from traditional exegetical models to rational and reformist interpretations of the Qur’an, and continues to hold significant relevance for contemporary scholarship in Islamic studies.